Instant-Ylid: ein lagerfähiges und gebrauchsfertiges Wittig-Reagenz - Manfred Schlosser; Bruno Schaub (CHIMIA)
Mixtures prepared from alkyltriphenylphosphonium bromides and powdered sodium amide can be stored indefinitely. Upon addition of an ethereal solvent, however, they immediately generate the ylide which then may be reacted with aldehydes, ketones or formiates. The use of such “instant-ylid” mixtures offers distinct advantages over conventional Wittig procedures: optimum yields (even with enolisable ketones), highest cis/trans-ratios, largest range of applicability, shortest reaction times and easiest handling.